2016
DOI: 10.3390/nu8020091
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Flavonols Intake and Risk of Esophageal and Gastric Cancer: A Meta-Analysis of Epidemiological Studies

Abstract: Background: Esophageal cancer (EC) and gastric cancer (GC) are common cancers and leading causes of cancer deaths worldwide. Many studies have investigated the association between dietary flavonols intake and the risk of EC and GC, but the results are inconsistent. Hence, we conducted a systematic analysis of relevant population-based studies to assess the association and derive a more precise estimation. Methods: The Cochrane, PubMed and Embase databases were searched to identify articles published through Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 42 publications
1
22
0
3
Order By: Relevance
“…To date, meta-analyses have mainly focused on dietary flavonoids and breast cancer [ 29 ], lung cancer [ 30 ], and stomach and colorectal cancer [ 16 ]. The latest meta-analysis found no significant association between dietary flavonols intake and the risk of esophageal cancer in four studies [ 31 ]. The results of published epidemiological studies are controversial because most of the studies found no significant association between dietary flavonoid intake and esophageal cancer; whereas two studies showed that flavonoids were associated with had significant reductions in the risk of esophageal cancer [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, meta-analyses have mainly focused on dietary flavonoids and breast cancer [ 29 ], lung cancer [ 30 ], and stomach and colorectal cancer [ 16 ]. The latest meta-analysis found no significant association between dietary flavonols intake and the risk of esophageal cancer in four studies [ 31 ]. The results of published epidemiological studies are controversial because most of the studies found no significant association between dietary flavonoid intake and esophageal cancer; whereas two studies showed that flavonoids were associated with had significant reductions in the risk of esophageal cancer [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another Swedish population-based case–control study including 505 GC cases reported an inverse association with the flavonol quercetin [ 41 ]. Likewise, a meta-analysis involving 4593 cases supported the evidence of an inverse association between flavonols and GC risk [ 42 ].…”
Section: Discussionmentioning
confidence: 97%
“…Based on the results of our study, the consumption of salt, hot tea, soft drinks, Deli meats and saturated oil in the patients' group was significantly higher than that of the control group. Some studies have demonstrated that inappropriate nutritional behaviors such as high salt intake and hot drinks can be associated with the incidence of gastrointestinal cancers (Shivanna and Urooj, 2016;Xie et al, 2016). It has been shown that the consumption of highly concentrated salt can induce mucosal membrane damage, stimulate inflammatory responses and increase the proliferation of epithelial cells, and subsequently increase the probability of carcinogenic genetic mutations (Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%